2007
DOI: 10.1016/j.devcel.2007.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein-Heparan Sulfate Interactions in the Hh Pathway

Abstract: The Drosophila lipoprotein particle, Lipophorin, bears lipid-linked morphogens on its surface and is required for long-range signaling activity of Wingless and Hedgehog. Heparan sulfate proteoglycans are also critical for trafficking and signaling of these morphogens. Here we show that Lipophorin interacts with the heparan sulfate moieties of the glypicans Dally and Dally-like. Membrane-associated glypicans can recruit Lipophorin to disc tissue, and remain associated with these particles after they are release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
171
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(177 citation statements)
references
References 51 publications
5
171
1
Order By: Relevance
“…Movement of Hh proteins in the extracellular space is limited by covalent lipid modifications at both aminoand carboxyl-terminal domains (38,39). Lipid-modified Hh proteins are secreted as multimers that interact with heparan sulfate proteoglycans (HSPGs), which further restricts their movement (40,41). Our data suggest that Shh protein is concentrated between the media and adventitia because of local synthesis, secretion, and retention of Shh multimers by ECM components, such as the HSPG perlecan (42), in the artery wall.…”
Section: Discussionmentioning
confidence: 99%
“…Movement of Hh proteins in the extracellular space is limited by covalent lipid modifications at both aminoand carboxyl-terminal domains (38,39). Lipid-modified Hh proteins are secreted as multimers that interact with heparan sulfate proteoglycans (HSPGs), which further restricts their movement (40,41). Our data suggest that Shh protein is concentrated between the media and adventitia because of local synthesis, secretion, and retention of Shh multimers by ECM components, such as the HSPG perlecan (42), in the artery wall.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an enhanced interaction with glypican-3 would further reduce the signaling capacity via PTC1. Studies have suggested that HSPGs can facilitate Hh movement by means of lipoprotein binding in the extracellular matrix and can antagonize PTC-mediated Hh sequestration, thereby promoting long-range movement [41,42]. Furthermore, a recent study has shown that Hh monomers can form nanoscale oligomers that are selectively enriched in visible clusters containing HSPGs [43].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that lipid-linked proteins (including GPIlinked, cholesterol-modified and palmitoylated proteins) associate with Lpp, permitting their local mobilization (Panáková et al, 2005;Eugster et al, 2007 (Fig. 4 A).…”
Section: Apol-tevmentioning
confidence: 92%
“…Antibodies were diluted as follows: anti-HA16B12 1:1500 (Santa Cruz Biotechnology), anti-Elav7E8A10 1:1500 [Developmental Studies Hybridoma Bank (DSHB), University of Iowa, Iowa City, IA], anti-HRPCy5 1:500 (Dianova), anti-Lpp (Eugster et al, 2007) (Wang and Holmgren, 1999), anti-Dpn (1:30) (Boone and Doe, 2008), anti-Myc 1:1000 (Gramsch), anti-Prospero-MR1A 1:750 (DSHB), anti-Repo8D12 1:500 (DSHB) and anti-phosphohistone H3 6G3 1:1500 (Cell Signaling Technology). Phalloidin-Cy5 1:200 (Invitrogen) and FilipinIII 1:500 (Sigma).…”
Section: Immunohistochemistrymentioning
confidence: 99%